2021
DOI: 10.4018/978-1-7998-8426-2.ch012
|View full text |Cite
|
Sign up to set email alerts
|

Service Only Supply Chain

Abstract: Broadly, the sustainable practices for the manufacturing supply chain are considered as environmental, social, and economic practices. But due to different characteristics of services, the above-mentioned sustainable practices are necessary. Beyond these practices, some other novel practices are necessary for the service context. This chapter discusses the novel sustainable practices for the service only supply chain (SOSC). The discussed sustainable practices will enhance the understanding of sustainable prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The latent variables have a significant positive contribution to the mediating variable. The mediating variable "organizational resilience" also has a substantial effect on the dependent variable firm performance (Nagariya et al, 2021c). As per the survey conducted and analysis carried out for the final 311 responses received from different MSMEs, it is concluded that the identified latent variables play a significant role in the "firm performance" with the mediating effect of the variable' organizational resilience."…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The latent variables have a significant positive contribution to the mediating variable. The mediating variable "organizational resilience" also has a substantial effect on the dependent variable firm performance (Nagariya et al, 2021c). As per the survey conducted and analysis carried out for the final 311 responses received from different MSMEs, it is concluded that the identified latent variables play a significant role in the "firm performance" with the mediating effect of the variable' organizational resilience."…”
Section: Discussionmentioning
confidence: 92%
“…The latent variables have a significant positive contribution to the mediating variable. The mediating variable “organizational resilience” also has a substantial effect on the dependent variable firm performance (Nagariya et al. , 2021c).…”
Section: Discussionmentioning
confidence: 99%
“…, 2022; Nagariya et al. , 2021c, d and e). Fuzzy TOPSIS method also ranks B2, B3 and B13 as rank 8, 7 and 4, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Sustainability practices (hereafter SP) are used by organizations to prevent their actions from being harmful to the environment, society, and stakeholders, while at the same time remaining economically viable (Nagariya et al, 2021). In fact, these three aspects (environmental protection, social equity, and economic viability) should be borne in mind when designing and developing SP, which can be internal (when developed internally within the company's boundaries) or external (when developed with the company's partners) (Macchion et al, 2018).…”
Section: Introductionmentioning
confidence: 99%